2023
DOI: 10.1111/jre.13111
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and its association to endothelial dysfunction and clinical changes in limited systemic sclerosis: A case–control study

Abstract: Objectives Periodontal disease occurs frequently in patients with limited cutaneous systemic sclerosis (lcSSc) while data about underlying pathways contributing to periodontal changes are scarce. The aim of this study was to evaluate periodontal disease and to investigate its association with endothelial dysfunction and clinical changes in patients with lcSSc. Methods In 38 lcSSc patients and 38 controls, periodontal status was evaluated by disease‐specific questionnaire, dental examination including bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Patients' characteristics have been described elsewhere (9,12). Median uric acid levels were 4.6 mg/dL (3.9-5.4 mg/dl 25th-75th percentile) in patients with lcSSc and 4.3 mg/dL (3.7-5.3 mg/dL 25th-75th percentile) in controls (p = 0.313).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients' characteristics have been described elsewhere (9,12). Median uric acid levels were 4.6 mg/dL (3.9-5.4 mg/dl 25th-75th percentile) in patients with lcSSc and 4.3 mg/dL (3.7-5.3 mg/dL 25th-75th percentile) in controls (p = 0.313).…”
Section: Resultsmentioning
confidence: 99%
“…Parameters of periodontal disease, including pocket depth, plaque index, bleeding on probing (BOP), bone loss and bone support ratio were evaluated by dental and oral examinations with a dentist's mirror and a periodontal probe as well as by digital dental panoramic radiograph (Orthophos XG 3D, Dentsply Sirona, Charlotte, USA) (35,36). Detailed information about the measurement methods of vasculopathy-related and SSc-specific clinical changes have been previously published (9,12).…”
Section: Vasculopathy-related and Ssc-specific Clinical Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported data have indicated a relationship between periodontitis and SSc [ 2 ], mostly with the latter’s diffuse form [ 9 ]. Twelve case-control studies investigating periodontal conditions and their related risk factors in SSc patients were identified [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Only six studies revealed an association between the two diseases, with SSc being positively correlated with periodontitis [ 9 , 13 , 16 , 19 , 20 ] or periodontitis-related parameters [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twelve case-control studies investigating periodontal conditions and their related risk factors in SSc patients were identified [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Only six studies revealed an association between the two diseases, with SSc being positively correlated with periodontitis [ 9 , 13 , 16 , 19 , 20 ] or periodontitis-related parameters [ 14 ]. A very recent meta-analysis including some of the above-mentioned reports highlighted that periodontitis was more common in SSc patients [odds ratio (OR) 7.007; 95% confidence interval (CI) 3.529, 13.915)] and was associated with more changes of clinical parameters such as probing depth (PD) [standard mean difference (SMD) 3.101; 95% CI 1.374, 4.829] and clinical attachment loss (CAL) (SMD 2.584; 95% CI 0.321, 4.846) [ 2 ].…”
Section: Introductionmentioning
confidence: 99%